Human Monoclonal Antibodies Methods and Protocols - Steinitz, Michael.; Steinitz, Michael. (Methods in Molecular Biology,, 2014)
The introduction of monoclonal antibodies revolutionized immunology. The development of human monoclonal antibodies was inspired primarily by the enormous clinical benefits promised by these reagents which can be used as anti-inflammatory reagents, anti-tumor reagents and reagents for passive immunization in a variety of pathologies. Human Monoclonal Antibodies: Methods and Protocols presents technical protocols of cellular and molecular methods for the production, purification and application of human monoclonal antibodies, as well as review articles on related topics of human monoclonal and polyclonal antibodies. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Human Monoclonal Antibodies: Methods and Protocols seeks to serve both professionals and novices with its well-honed methodologies which will prove invaluable in a clinical setting.